Network and machine learning analyses of estuarine microbial communities along a freshwater-marine mixed gradient. (31st October 2022) - Da Silva, R.R.P.; White, C.A.; Bowman, J.P.; Bodrossy, L.; Bissett, A.; Revill, A.; Eriksen, R.; Ross, D.J.
Abstract: Microbial communities are important elements in the marine environment, contributing to nutrient cycling and biogeochemical processes. Estuaries comprise environments exhibiting characteristics from freshwater to marine, leading to distinct microbial communities across this environmental gradient. Here, we examine the spatial dynamics of microbial communities in Macquarie Harbour, an estuarine system on the West coast of Tasmania, Australia. Water was sampled along the estuary to explore the structure and composition of the microbial communities using 16S/18S rRNA gene amplicon sequencing. Multivariate analyses showed environmental variables and community compositions varying along a longitudinal (river to adjacent ocean) gradient at the surface. In the Harbour, differences in the microbial community were observed between surface (0–1 m) and intermediate depths (4.5–11 m depth). The results of differential abundance, network and Partial Least Square analyses suggest that Macquarie Harbour is a mixing zone, where the distributions of archaeal, bacterial and eukaryotic communities are influenced by oceanic and riverine inputs. These results provide critical insights into the Macquarie Harbour environment and the importance of understanding the role of microbial communities for similar systems elsewhere. Highlights: Network and machine learning revealed the microbial community structure in a highly stratified aquatic environment. Environmental variables and community compositions varied along a longitudinal (river to adjacent ocean) gradient. Oceanic and riverine inputs contribute to differences in the composition of microbial communities. Pelagic heterotrophic microorganisms may play important roles in the nutrient cycle in the Macquarie Harbour.